Teacher Stress and Burnout in Islamic Elementary Schools: The Role of Human Resource Interventions - Ikhfanudin Ikhfanudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The teaching profession can be a profession that has a high potential for stress and fatigue, especially teachers in early childhood, both in elementary schools and kindergartens. With the burden on teachers as teachers already quite heavy, then there are also certain policies that make the pressure even worse. So the potential for stress is even higher. Not to mention the main economic factor for honorary teachers which is still considered very low, even far from the minimum wage. There needs to be a suitable solution for this. This research uses a qualitative approach with descriptive analysis methods. The object of this research is the class teacher at Takhassus Al Qur'an Elementary School Al Hikmah Islamic Boarding School. Data collection was carried out by interviews, observation and documentation. This research shows that work stress can be minimized with human resource intervention.